2014
DOI: 10.2319/060114-392.1
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and dental effects of molar distalization using a modified palatal anchorage plate in adolescents

Abstract: Objective: To evaluate and compare skeletal effects and the amount of molar distalization in maxilla using modified palatal anchorage plate (MPAP) vs headgear appliances in adolescent patients. Materials and Methods: Pre-and posttreatment lateral cephalograms of 45 Class II malocclusion patients were analyzed; 24 were treated with MPAP appliances (age, 12.4 years) and 21 with headgear (age, 12.1 years). Fixed orthodontic treatment started with the distalization process in both groups. Thirty-two variables were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
4
26
1
Order By: Relevance
“…13,14 Recently, MPAPs have effectively distalized the entire dental arch and showed remodeling of the anterior area of the maxilla. 13,14,16,27 The changes seen in patient 1 agree with these results. Although previous studies showed that MPAPs usually result in intrusion of the maxillary first molars, 15,16 in our patient and similar to the study of Sa'aed et al, 27 the intrusion was masked by downward growth of the maxilla, resulting in extrusion of the molars.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…13,14 Recently, MPAPs have effectively distalized the entire dental arch and showed remodeling of the anterior area of the maxilla. 13,14,16,27 The changes seen in patient 1 agree with these results. Although previous studies showed that MPAPs usually result in intrusion of the maxillary first molars, 15,16 in our patient and similar to the study of Sa'aed et al, 27 the intrusion was masked by downward growth of the maxilla, resulting in extrusion of the molars.…”
Section: Discussionsupporting
confidence: 92%
“…14,16,27 The orthopedic effect of the MPAP for maxillary protraction must be verified in future studies with large samples.…”
Section: Discussionmentioning
confidence: 98%
“…[13][14][15] Recently, the use of the modified C-palatal plate (MCPP) for maxillary arch distalization was reported for Class II corrections in both adolescents and adults. 1,[16][17][18][19][20][21] The MCPP is a distalization appliance with a large range of action that can be easily placed without raising a flap. It also has been shown to have the capability of vertical control during distalization.…”
Section: Introductionmentioning
confidence: 99%
“…17 Another study reported 3.1 mm of molar distalization with 1.58 of distal tipping and 1.7 mm of extrusion using the MCPP. 4 However, in the current study, the molars were distalized 3.2 mm with 3.18 of distal tipping and 1.3 mm of intrusion. These differences might be because the previous studies were performed on adolescents using a 2D evaluation method.…”
Section: Discussionmentioning
confidence: 57%
“…3 Its treatment effects, as reported by the same research group, showed significant amounts of distalization and intrusion with minimal distal tipping of the first molar. 4,5 However, accurate evaluation of the root position is very difficult to perform on two-dimensional (2D) lateral cephalograms because of superimposition and projection factors.…”
Section: Introductionmentioning
confidence: 99%